Which one of the following is a simplification of

1 Like

In order to solve this question, we need to know the **difference of two squares**:

a^2 -b^2 = (a-b)(a+b)

\frac{2}{x^2 -1} - \frac{1}{x-1} = \frac{2}{(x-1)(x+1)} - \frac{1}{x-1} = \frac{1}{x-1}( \frac{2}{(x+1)} -1) = \frac{1}{x-1}( \frac{2 - (x+1)}{(x+1)} ) = \frac{1}{x-1} \frac{2 -x -1)}{(x+1)}=

\frac{1}{x-1} \frac{1 -x }{(x+1)} = \frac{1}{x-1} (-1)\frac{x-1}{x+1} = -\frac{1}{x+1}.

So the answer to this question is **(A)** -\frac{1}{x+1}.

4 Likes